An Analysis of Speaking Anxiety Experienced by Tourism And Hospitality Department Students of SMKN 6 Padang - Laksmi Riadi Ningsih; Sitti Fatimah (Universitas Negeri Padang, 2020)
Speaking is one of the ways to communicate that is mostly used by people to interact with others. However, some people feel anxious to speak in English. This research was conducted to find out the factor and the level of speaking anxiety experienced by Tourism and Hospitality students of SMKN 6 Padang. The subject of this research was 59 students from grade 12th of tourism and hospitality department. The data was collected by using quantitative descriptive method. The research instruments were questionnaire and interview. There were two questionnaires used such as FLCAS and FLSAS questionnaire. Each questionnaire consists of 33 statements. Based on the data analysis, it was found the dominant factors of students’ speaking anxiety was fear of speaking test. On the other hand, the level of students’ speaking anxiety from two questionnaires were in medium level with percentage from FLCAS was 75%, and from FLSAS questionnaire was 71%. It can be concluded that students felt anxious because of some causes such as mispronunciation, afraid of making mistakes, lack of vocabulary, and think that friend is better than themselves.